ANALYSIS OF PHYSICAL PROPERTIES OF OPEN CLUSTER M45 BY CCD PHOTOMETRY TECHNIQUE - Chaiwarakorn, Sommkorn; Sukkaew, Adulsman; Chemasalae, Salmee; Thassana, Chewa (Jurnal Sains Dasar, 2018)
In this work, the open cluster M45 was observed by CCD photometry technique using a standard UBV filter via Ritchey-Chretien Telescope, which has a diameter of 0.5 meter. The author measured data have to be analyzed by using IRIS program, shows that the true apparent magnitudes of the 30 stars in the visual and blue wavelength bands range from 8.244 to 9.000, and 8.278 to 9.005, absolute magnitudes in the visual and blue wavelength bands range from 2.544 to 3.300, and 2.578 to 3.338, respectively. The color indices range from -0.773 to 0.955. And standard published color indices and magnitude diagrams for the 30 stars were used. In order to obtain a Hertzsprung - Russell diagram (H-R diagram) of certain stars, was sufficient to calculate the distance of the open cluster M45 from earth at 138.038 parsecs, and its age at 1.6 x 108 years. Keywords: cluster M45, CCD photometry, IRIS proggram